The Students’ Ability in Reading Comprehension of TOEFL Test For The EFL Learners - Selamet Riadi Jaelani; Hizbul Wathoni; Bambang Purnama; Hanofi Harianto; Safar Wadi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2022)
The objectives of the research are to know the students’ ability in reading comprehension of TOEFL test for the EFL Learners. This study was categorized as a descriptive quantitative research. This study was conducted at the eighth semester students of Hamzanwadi University. The population of this study was 144 students from 3 classes and the sampling method was purposive sampling. The sample of this study was 30 students. The research instrument used to collect data was reading comprehension of TOEFL test. The collected data were submitted to descriptive statistic by using SPSS 22 for windows. The mean score of the test was 4.17, it categorized into low. Based on that result, the EFL Learners did not have good ability in finding main ideas, references, and meaning of words on reading of TOEFL test. Meanwhile, the mean score in finding information was 7.2 and inference was 6.4. So, the EFL Learners did not have good ability in finding information and inference.AbstrakTujuan dari penelitian ini adalah untuk mengetahui kemampuan mahasiswa dalam membaca pemahaman tes TOEFL untuk Peserta Didik EFL. Penelitian ini dikategorikan sebagai penelitian kuantitatif deskriptif. Penelitian ini dilakukan pada mahasiswa semester delapan Universitas Hamzanwadi. Populasi penelitian ini adalah 144 mahasiswa dari 3 kelas dan metode sampling menggunakan purposive sampling. Sampel penelitian ini adalah 30 mahasiswa. Instrumen penelitian yang digunakan untuk mengumpulkan data adalah pemahaman membaca TOEFL. Data yang dikumpulkan diserahkan ke statistik deskriptif dengan menggunakan SPSS 22 untuk windows. Skor rata-rata tes adalah 4,17, dimana dikategorikan ke rendah. Berdasarkan hasil tersebut, Peserta Didik EFL tidak memiliki kemampuan yang baik dalam menemukan ide utama, referensi, dan makna kata pada tes pemahaman membaca TOEFL. Sementara itu, skor rata-rata dalam menemukan informasi adalah 7,2 dan kesimpulan adalah 6,4. Jadi, Peserta Didik EFL tidak memiliki kemampuan yang baik dalam menemukan informasi dan kesimpulan.